Studi Perbandingan Standar Pelayanan Kesehatan Antara Rumah Sakit Umum dan Rumah Sakit Swasta di Kota Kupang - Marini Sari Dewi Seger; Hendrik Toda (Research and Development Agency Ministry of Home Affairs, 2025)
Universal Health Coverage in Indonesia is implemented through the National Health Insurance (JKN) managed by BPJS Kesehatan. In East Nusa Tenggara, RSUD Prof. Dr. W. Z. Johannes and RSU Siloam Kupang serve as top referral centers for BPJS patients, yet variations in public service standards persist. In this study, the researcher used a sequential explanatory mixed-method design, combining quantitative factor analysis with qualitative exploration using NVivo. The study involved BPJS patients in inpatient, outpatient, and emergency units at RSUD Prof. Dr. W. Z. Johannes (n = 13,958) and RSU Siloam Kupang (n = 10,192) during 2023, with stratified samples surveyed and interviewed on dimensions of public service standards. Factor analysis indicated RSUD Prof. Dr. W. Z. Johannes excelled in requirements, procedures, and service time, while RSU Siloam Kupang outperformed in facilities, complaint handling, and performance evaluation. NVivo outputs highlighted recurring issues of “complaints,” “time,” and “information,” signaling systemic gaps in both institutions. RSUD Prof. Dr. W. Z. Johannes reflects stronger procedural clarity and timeliness consistent with public service norms but requires modernization of infrastructure and complaint systems. RSU Siloam Kupang demonstrates superior physical resources and digital complaint management yet faces delays and complex administrative flows for BPJS patients. Institutional structures and managerial approaches shape these differences, emphasizing the need for alignment with Law No. 25/2009 and New Public Service principles to ensure equitable, responsive care.